Quiet places a look at ecotourism in the Philippines - Conti, Joey.; Chiu, Stella; Honasan, Alya. ([Makati] Bookmark Video, 1998)
This documentary explains the concepts and shows examples of ecotourism in the Philippines, focusing on marine and riverine settings such as the Tubbataha Reefs, Anilao, Bais, the Bohol rivers, the Agusan marsh, Donsol, the Batanes islands, Lake Sebu, Honda Bay, Coron, and the Turtle Islands.
VHS.
Keywords: Tourism